The integrating and disintegrating role of Silesian art between 1526 and 1740 - Oszczanowski, Piotr (Wydawnictwo eBooki.com.pl, 2014)
The issue of Silesian art is a methodological matter, one which the scholars are studying for nearly a century. Results of research reinforce the belief that Silesian art – especially at the end of the 14th and beginning of the 15th century, as well as in the Baroque – formed distinct qualities determining it’s unconventional worth, allowing it to be included with the artistic achievements of the continent. An attempt to answer which factors shaped the identity of the early modern Silesian art leads to two groups of factors, specifically cohesive and disruptive. Among the cohesive factors are historical events, the Catholic-Lutheran conflict, which, in Silesia lasted all through the Early Modern Period. Also of importance was the tradition of the Middle Ages and the availability of materials used by local artists (e.g. glass, sandstone). Among these works of particular importance are the workshops creating for the Cistercian monasteries (in Lubiąż, Krzeszów, Henryków, and Trzebnica). This resulted in the creation of a distinct mystic trend. It was associated with the development of Silesian iconographical tradition, e.g. in the local portrayal of saints and religious imagery. Among the factors disruptive to the artistic identity of Silesia is being a part of common artistic tradition (the western civilisation) and ideological (Christianity). This led to universal content of both lay and religious artworks. Silesia’s location at the hub of many transportation routes as well as on the border between two large states made it an area, which “absorbed” external influence. Silesian art became a universal „product” due to its dependence on external sources, rules imposed by a specific monastic order as well as rules of the authorities.
Keywords: Silesia; Renaissance; Baroque; art and craft; art